Perjalanan Kapitalisme Informal Pada Usaha Thrifting Melalui Interpretasi Mitos (Interaksionalisme Simbolik, Herbert Mead) - Dwi Wahyu Maulana Putra; Isna Fitrotul Kamila; Nazwa Reina Salsabila (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
This research investigates the course of informal capitalism in the thrifting industry and the role of myth and symbolism in shaping business culture and practices in this context. With reference to Herbert Mead's symbolic interactionalism framework, this study uncovers how symbolism and the impact of sustainability myths, and sellers and buyers' perceptions of seller and buyer preferences and thrift store marketing strategies. In combining social and economic aspects, this research provides a deep insight into the complex dynamics of thrifting industries. The results of this research enrich our understanding of the impact of social and economic change in contemporary society and highlight the economic and cultural complexities in the thrifting industry that are increasingly sustainable and closely linked to myths and symbolism